Warm Foot Soak Intervention for Hyperthermia in DHF (Dengue Hemorrhagic Fever) Patients: A Case Study at Bhayangkara Hospital, Lampung - Hardono, Hardono; Inggit Laras Tika; Sadhana, Wisnu; HS, Asril (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Warm water foot soak therapy presents a viable alternative for managing fever in patients who experience discomfort with conventional compress methods. This scientific paper aims to provide nursing care for patients with Dengue Hemorrhagic Fever (DHF) experiencing hyperthermia, utilizing warm water foot soak interventions in the inpatient ward of Bhayangkara Hospital, Lampung. The nursing care approach follows the nursing process framework, focusing on direct nursing interventions. The subject of care consisted of DHF patients in the inpatient unit, with the primary intervention being warm water foot soaking. Data collection tools included physical examinations and standardized nursing assessment formats (KMB), with data gathered through interviews, observation, and physical examination. During the assessment phase, the patient exhibited classic signs of DHF, including high-grade fever. A nursing diagnosis of hyperthermia was established. The primary intervention implemented was a warm water foot soak. After three days of therapy, the patient's body temperature decreased to 37.2°C, and the patient reported improved comfort and no further complications. These findings suggest that warm water foot soaking is an effective supportive intervention for managing hyperthermia in DHF patients. It is recommended that patients and their families be encouraged to understand and apply simple, non-pharmacological interventions such as warm foot soaks alongside adherence to prescribed medical treatment.